Combining Categories of Management Control Tools for High Performance of Start-ups - Carraro, Wendy Beatriz Witt Haddad; Meneses, Raquel; Brito, Carlos (Review of Business Management, 2019)
Purpose – This study aims is to examine possible combinations of management control tools that are likely to lead to high performance in start-ups. Design/methodology/approach – Personal interviews were conducted with entrepreneurs from 45 start-ups established in Technology Parks of University Centers in Portugal. Based on practices from different categories of organizational analysis, it was used the fuzzy Qualitative Comparative Analysis (fsQCA) methodology. Findings – To achieve high performance, management controls are required for Clients, Strategy, Information Systems, Performance, Risks and Budget. The Client and Budget categories presented the greatest consistency in meeting the proposed condition. In addition, the results generated two combinations of conditions for the high performance of net income. Originality/value – The combination of different management control practices contributes to the success of the business, especially when it relates to the organization’s strategic practices. The use of management control tools becomes a priority for companies that wish to cope with the challenges raised by corporate uncertainties, especially in start-up companies, ensuring the sustainable growth of these businesses.